GABAmimetic intravenous anaesthetics inhibit spontaneous Ca 2+-oscillations in cultured hippocampal neurons - Sinner, Barbara; Friedrich, Oliver; Zink, Wolfgang; Fink, Rainer; Graf, Bernhard (Acta Anaesthesiologica Scandinavica, 2006)
BACKGROUND Spontaneous Ca2+ -oscillations are a possible mechanism of Ca2+ -mediated signal transduction in neurons. They develop by a periodical interplay of Ca2+, which enters the neuron from the extracellular medium and triggers Ca2+ release from the endoplasmic reticulum (ER). Ca2+ -oscillations are terminated by reuptake into the ER or plasmalemmal extrusion. Spontaneous Ca2+ -oscillations are glutamate dependent and appear to be responsible for neuronal plasticity and integration of information. Here, we examined the role of the gamma-aminobutyric acid (GABAA) receptor on spontaneous Ca2+ -oscillations and studied the effects of the anaesthetics midazolam, thiopental and the non-anesthetic barbituric acid on spontaneous Ca2+ -oscillations. METHODS Hippocampal neuronal cell cultures of 19-day-old embryonic Wistar rats 17-18 days in culture were loaded with the Ca2+ -sensitive dye Fura-2AM. Experiments were performed using dual wave-length excitation fluorescence microscopy and calibration constants were obtained from in situ calibration. RESULTS Spontaneous Ca2+ -oscillations are influenced by the GABAA receptor. The intravenous anaesthetics midazolam and thiopental suppressed the amplitude and frequency reversibly in a dose-dependent manner with EC50 in clinically relevant concentrations. This effect was mediated via the GABAA receptor as it could be reversed by the GABAA receptor antagonist bicuculline. In contrast, the application of barbituric acid had no effects on the spontaneous Ca2+ -oscillations. CONCLUSION Spontaneous Ca2+ -oscillations are influenced by the GABAA receptor. Spontaneous Ca2+ -oscillations might represent an interesting model system to study anaesthetic mechanisms on neuronal information processing.
Keywords: Barbituric acid; GABAa receptor; Midazolam; Spontaneous Ca2+-oscillations; Thiopental